Luminescent properties and X-ray photoelectron spectroscopy study of ZnAl2O4:Ce3+,Tb3+ phosphor - Tshabalala, K. G.; Cho, S. -H.; Park, J. -K.; Pitale, Shreyas S.; Nagpure, I. M.; Kroon, R. E.; Swart, H. C.; Ntwaeaborwa, O. M. (ELSEVIER SCIENCE SA, 2011)
Cerium (Ce3+)- and terbium (Tb3+) co-doped zinc aluminate (ZnAl2O4) nanocrystals were successfully prepared by a combustion method using urea as fuel. The as-prepared samples were annealed in hydrogen atmosphere to improve their optical properties and crystallinity. The structure and morphology of the samples analyzed using X-ray diffraction (XRD) and high resolution transmission electron microscopy (HRTEM) showed that ZnAl2O4 crystallized in a well known cubic spinel structure. As deduced from X-ray photoelectron spectroscopy (XPS) data, there was partial inversion of cations in as-prepared (unannealed) samples implying that the ZnAl2O4 did not crystallize in a cubic normal spinel. Instead, the XPS data demonstrated possible structural readjustment from inverse to normal spinel after annealing. The excitation and emission data collected when ZnAl2O4:Ce3+, Tb3+ samples, with different concentrations of Ce3+ and Tb3+ ions, were excited at different wavelengths showed that green emission of Tb3+ was sensitized by Ce3+, i.e. there was energy transfer from Ce3+ to Tb3+ resulting in improvement of green emission from Tb3+. This study therefore, sets out to discuss the sensitizing effect of Ce3+ and the effect of annealing on the structure of ZnAl2O4:Ce3+, Tb3+. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: THIN-FILM; ZNAL2O4; NANOCRYSTALLINE; SPINEL; SCINTILLATION; EU3+